Application of SNCR Denitrification Technology for Flue Gas From Cement Kilns: A Mini Review - Zhou, Qi-Ying; Wang, Peng-Chen; Jiang, Xia; Jiang, Wen-Ju (Recent Innovations in Chemical Engineering, 2015)
Currently, the emission amount of nitrogen oxide (NOx) from the cement industry accounts for about 10-12% of total emissions in China, and the cement industry has become the third biggest source of NOx, following thermal power plants and vehicles. Thus, the task for controlling NOx emission from the cement industry is very urgent. Selective non-catalytic reduction (SNCR) denitrification technology has many advantages, such as low investment cost, short construction period, simple facilities and low operating cost, etc. This technology is suitable for the reconstruction of the existing cement production lines and the matching construction of the new cement production lines, and is currently considered to be the best denitrification technique for cement kilns. The basic principle and process of SNCR in cement kilns were analyzed and the key points of SNCR denitrification process in cement kilns were summarized, including the proper reaction temperature window (850 1050°C), mixing of reducing agent and flue gas, NH3/NOx mole ratio, residence time, the control of ammonia escape and the effect of calcium base powder. The current status of SNCR simulation and industrial application in cement kilns were also comprehensively analyzed, together with the future development direction of SNCR denitrification technology in cement industry.
Keywords: Calcium base powder